Energy efficiency of conventional air conditioning systems in light of climate change - Ghaith, Fawaz Khaled (Journal of engineering sciences and information technology, 2023)
The energy used in a country’s economy is very important to its development. Over the years, the electricity and ventilation consumption of buildings have increased. People’s concerns about the quality of their indoor environment are also increasing. Most buildings have air conditioning and ventilation systems that are designed to provide an environment that’s comfortable and healthy for the occupants. This is done through the use of ventilation. In addition to improving the indoor air quality, it can also help prevent people from experiencing discomfort. Studies have shown that about 60% of office buildings’ energy consumption is attributed to the use of air conditioning systems. These systems provide cool air to the spaces while keeping the temperature controlled. A VAV system can meet the health criterion and the IAQ by supplying enough fresh air to meet national standards. A conventional AC system requires a refrigeration plant and a network of pipes to deliver cold water to the spaces. Since air-cooled chiller systems have a flexible design, they are commonly used in commercial buildings. They can provide a cooling effect that’s significantly higher than that of water-cooled units. Compared to water cooling systems, air-cooled units are more energy-efficient. This is because the head pressure control of the system ensures that the pressure is kept high. The use of air conditioning has been one of the biggest sources of electrical energy consumption worldwide. It has contributed over 10% of the total energy produced, and it contributes to the harmful effects of climate change. Climate change is a growing concern that will require the production and use of more air conditioning units. This has necessitated the development of a comprehensive research to address this issue.